Seroprevalence of Coxiella burnetii in selected populations of domestic ruminants in Newfoundland - Hatchette, Todd (2002)
The seroprevalence of Coxiella burnetii among cattle, sheep, and goats in Newfoundland was determined by microimmunofluorescence. Seropositivity to phase II antigen increased in sheep from 3.1% in 1997 to 23.5% in 1999–2000 (P < 0.001). Cows (24%) had antibodies to phase I antigen; goats (15.6%) had antibodies to phase II antigen. Seroprevalence of C. burnetii is increasing among sheep.